STRATEGI ADAPTASI NELAYAN CIREBON, JAWA BARAT - Eko Sri Wiyono (Buletin PSP, 2008)
Key of fisheries management is how to manage fishing efforts which is operated by fisherman. To understand how fisherman operate their fishing gear, understanding on their adaptation pattern to changing of external factors are needed. In this study, adaptation strategy of garuk’s fisherman in Cirebon West Java to response external factors changing was studied. Results of this study showed that fisherman and captain tend to have similar adaptation pattern. Conversely, fisherman owners have different adaptation. In detail, this paper will discuss how fisherman adapts to some external factors which influence their fishing incomes.